2019
DOI: 10.35580/chemica.v19i2.12772
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kualitatif Fitikomia Kandungan Flavonoid Ekstrak Kayu Sepang (Caesalpinia Sappan L.) dari Ekstraksi Metode Ultrasonic Assisted Solvent Extraction

Abstract: ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi isolat dari ekstrak kayu sepang dengan menguji keberadaan kandungan Flavonoid pada ekstrak. Isolasi dilakukan dengan melakukan ekstraksi menggunakan sonikator yaitu Ultrasonic-Assisted Solvent Extraction dengan menggunakan pelarut organik yaitu Etanol. Proses etanolik ini digunakan untuk mengisolasi senyawa flavonoid pada kayu sepang dengan menggunakan konsentrasi pelarut yang optimum dengan variasi konsentrasi pelarut 85%, 90%, 95%, dan 99% serta v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Pertamawati et al, (2017) in her research on secondary metabolite content in sappan wood also found the presence of phenolics, triterpenoids, flavonoids, and alkaloids. Flavonoids were discovered in secang wood extracted using an ultrasonic wave assisted extraction method (Asfar & Yasser, 2019). Terpenoids, flavonoids, and phenolics are secondary metabolites discovered in wood ethanol extract cups.…”
Section: Resultsmentioning
confidence: 99%
“…Pertamawati et al, (2017) in her research on secondary metabolite content in sappan wood also found the presence of phenolics, triterpenoids, flavonoids, and alkaloids. Flavonoids were discovered in secang wood extracted using an ultrasonic wave assisted extraction method (Asfar & Yasser, 2019). Terpenoids, flavonoids, and phenolics are secondary metabolites discovered in wood ethanol extract cups.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the polyphenol content of sappan wood at three pH values was 34.33% (pH 6), 13.70% (pH 7), and 12.66% (pH 8). The analysis findings show that pH 6 has the highest polyphenol level and that as pH increases, polyphenol content decreases [23].…”
Section: Phenolic Acidsmentioning
confidence: 96%
“…As an angiosperm plant, A. marina has a wide variety of flavonoids. The content of flavonoids in A. marina is much higher than several species of plants which are indicated to have potential as male anti-fertility agents, including Caesalpinia sappan which contains only one type of flavonoid [53]; Piper ornatum has three types of flavonoids [52]; and durian rind (Durio zibethinus) has nine types of flavonoids [48].…”
Section: Bioactive Compoundsmentioning
confidence: 99%